The Emergence of a Cooperative Amidst Economic Disruption: A Historical Narrative of Amul Coop in India - Abhijit Ghosh; Abhirup Chakrabarti (Administrative Sciences)
This study presents a process narrative of how cooperatives emerge during periods of economic disruption. Cooperative organizations are pluralistic and embedded in existing local economic contexts. Yet, the role that such organizations play can be pronounced when economic disruption occurs in the absence of well-established institutions to support cooperative ideology. This study uses the Structuration and Panarchy frameworks to examine the dynamics of Amul’s emergence, where individual producers organized against the existing structure of production in a period characterized by reorganization at the broader macro level. The study complements insights from economic and social perspectives while presenting a view of how individuals organize economically in the context of disruption. The narrative broadens the view of when collective action becomes possible and what explains sustained socio-economic value creation from such enterprises.